The proline cycle as an eukaryotic redox valve. (31st July 2021) - Zheng, Yao; Cabassa-Hourton, Cécile; Planchais, Séverine; Lebreton, Sandrine; Savouré, Arnould
Abstract: The amino acid proline has been known for many years to be a component of proteins as well as an osmolyte. Many recent studies have demonstrated that proline has other roles such as regulating redox balance and energy status. In animals and plants, the well-described proline cycle is concomitantly responsible for the preferential accumulation of proline and shuttling of redox equivalents from the cytosol to mitochondria. The impact of the proline cycle goes beyond regulating proline levels. In this review, we focus on recent evidence of how the proline cycle regulates redox status in relation to other redox shuttles. We discuss how the interconversion of proline and glutamate shuttles reducing power between cellular compartments. Spatial aspects of the proline cycle in the entire plant are considered in terms of proline transport between organs with different metabolic regimes (photosynthesis versus respiration). Furthermore, we highlight the importance of this shuttle in the regulation of energy and redox power in plants, through a particularly intricate coordination, notably between mitochondria and cytosol. Abstract : The proline cycle regulates energy and redox power in a shuttle mechanism with a valve function during plant development and in stress conditions.